Impact of biotechnology and nanotechnology on future bread improvement: An overview - GOEL, S; GREWAL, S; SINGH, K; DWIVEDI, N (The Indian Journal of Agricultural Sciences, 2019)
No crop contributes more to human flesh than the wheat that gives us our daily bread. A range of products can be processed from its flour, like bread, pasta, biscuits, chapatti etc, out of which bread is the most successful one. The end use quality of bread is mainly dependent on the quality and quantity of wheat seed storage proteins. There is a continuously increasing demand for good bread products both by the consumers and baking industry. To meet the growing demand of high quality nutritious bread with long shelf life a range of biotechnical and nanotechnical formulas have been employed to bring a new shape to food for the upcoming generation. Proteomics and transformation led to improved end product by modifying the wheat seed storage proteins for improved end products. Nanotechnology is an upcoming technology which is proving to be helpful in packaging and nutritional enhancement. Here, in this article, we have listed and focused on the techniques that would be helpful in enhancing bread quality and its nutritional status in future.